Examination of the relationship between the empathic tendencies and sleep quality of caregivers of cancer patients - Kerkez, Mujde; Yigit, Muhammet Faruk; Yazturk, Zeynep (Springer, 2025)
Purpose The present study aims to reveal the relationship between the empathic tendencies and sleep quality of caregivers of cancer patients. Material and method This cross-sectional study was conducted with caregivers of cancer patients registered in the oncology unit of a hospital between May and July 2024 (n = 346). The study data were collected using a sociodemographic information form, the Empathic Tendency Scale, and the Pittsburgh Sleep Quality Index. The data were analyzed using the Pearson correlation and hierarchical regression analyses as well as descriptive statistics. Findings. 59.5% of the participants were female and 88.2% lived with patients. 62.7% of the cancer patients were male and 61.1% were partially dependent in daily life activities. The caregivers had a mean total score of 70.58 +/- 16.85 on the Empathic Tendency Scale and a mean total score of 4.40 +/- 3.94 on the Pittsburgh Sleep Quality Index. It was found that there was a negative, strong, and statistically significant relationship between the mean total scores on the Empathic Tendency Scale and the Pittsburgh Sleep Quality Index (r = - 0.924; p < 0.001). According to the hierarchical regression model, certain sociodemographic features of the caregivers explained the variance in empathic tendency (Adj. R-2 = 0.607; p < 0.001), whereas when sleep quality components were added to the model, the variance in empathic tendency was explained (Adj. R-2 = 0.896; p < 0.001). Conclusion The caregivers of cancer patients were found to have high empathic tendencies, which was associated with high sleep quality. Furthermore, low empathic tendencies among the caregivers were found to be primarily associated with increasing length of care and advancing patient age. The findings underscore the pivotal role that empathic approaches play in enhancing the quality of care, underscoring the necessity for augmented interventions that prioritize a compassionate approach, and the management of empathy in caregivers of cancer patients.
Keywords: Caregivers; Empathy; Empathic tendency; Sleep quality; Quality of care